A survey of the extent of fabric knowledge of salespersons in selected department stores and fabric shops in Cubao, Quezon City. - Vesagas, Thessa Marie Santos; Ynchausti, Natividad S. (1992.)
The survey is on the extent of fabric knowledge of salespersons in Cubao, Quezon City. It aimed to find out how familiar salespersons are with fabrics they sell, as well as the influence of background data to their knowledge of fabrics. A survey-questionnaire was employed and designed to collect the necessary data. It consisted of three parts: the first part consisted of the background information on demographic variables. The second and third parts consisted of checklist and open-end questions to evaluate knowledge of fabrics. A total of thirty(30) questionnaires distributed to salespersons who have direct contact with customers. Statistical tools used were frequency trends and percentages for determining the respondents' ability to identify fabric names and properties. Test for independence was used for correlation the background data and fabric knowledge of salespersons. Findings of the study were as follows: 1. Salespersons were more familiar with fabric information in terms of fabric name, fiber content, fabric width, fabric weight and fabric color rather than the fabric construction and fabric finishes. 2. The length of employment was significantly correlated with the knowledge of salespersons on the fabrics they sell.
Thesis (BS Clothing Technology)--University of the Philippines Diliman.
Keywords: Textile industry -- Philippines